An assessment of procedures to remove exogenous Sr before 87Sr/86Sr analysis of wet archaeological wool textiles. (January 2015) - von Holstein, I.C.C.; Font, L.; Peacock, E.E.; Collins, M.J.; Davies, G.R.
Abstract: Strontium isotope analysis ( 87 Sr/ 86 Sr) has been employed as a provenancing tool for archaeological wool textiles. To date, the effect of post-depositional (soil burial environment) contamination on keratin samples, which contain ∼ppm concentrations of Sr, has not been rigorously investigated. We compared published methods for removing exogenous Sr from keratinous textiles, using either: (1) compressed N2 gas, (2) HF(aq) solution (with and without a strong oxidising agent to remove dyestuff) or (3) organic solvents. 87 Sr/ 86 Sr ratios and Sr contents were determined in undyed and madder-dyed/alum-mordanted moieties of the same wool textile, buried for up to three years in contrasting environments (marine sediment/fenland bog), and two archaeological textiles recovered in Iceland (one typical and one atypical of local manufacture). Undyed experimental samples had low Sr contents (0.07–0.29 ppm) that were increased by both dyeing (0.14–8.92 ppm) and soil burial (0.11–15.01 ppm). The efficacy of Sr removal was: HF(aq) + oxidising agent > organic solvents > HF(aq) > compressed N2 . Unburied samples showed little variation in 87 Sr/ 86 Sr ratio between cleaning methods (0.00006–0.00035); buried samples showed greater variation (0.00257–0.00713). Archaeological samples showed Sr contents greater than experimental soil burials (1–118 ppm), and 87 Sr/ 86 Sr values consistent with Icelandic groundwater (0.70357–0.70540). No cleaning methods retrieved original (unburied and undyed) 87 Sr/ 86 Sr ratios except treatment with compressed N2 in undyed samples. Exogenous Sr from the short term soil burial environment is probably mostly present as particulates. We conclude that 87 Sr/ 86 Sr ratios of archaeological wool textiles recovered from wet burial environments do not accurately reflect wool provenance even after cleaning with the methods investigated. Highlights: 87 Sr/ 86 Sr analysis has been proposed as a provenancing tool for archaeological wool. Methods to remove exogenous Sr due to dyeing and experimental burial were compared. Dyeing/mordanting and burial increased Sr content and 87 Sr/ 86 Sr ratio of fibres. Compressed N2 cleaning retrieved original 87 Sr/ 86 Sr ratios in undyed samples only. 87 Sr/ 86 Sr ratios of archaeological wool textiles did not reflect provenance.